2020
DOI: 10.3390/su12197959
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison between Collaborative and Individual Writings in Promoting Motivation and Language Acquisition

Abstract: The study refers to collaborative writing. The main objective of this study is to show the effects of collaborative writing in the acquisition of the English language upon students of non-compulsory secondary education. The applied study is grounded on a quantitative focus of correlational character and descriptive basis, while applying a quasi-experimental design with a control group (CG) and an experimental group (EG). The results show that there is a significant relation that favors the method of collaborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 63 publications
(92 reference statements)
1
4
0
Order By: Relevance
“…The results of this study revealed that the fundamental concepts of CT enhanced students' writing motivation in terms of self-efficacy beliefs, mastery goals, and performance goals more effectively than the conventional teaching method. The results of this study are consistent with those of [4,27], who have reported a significant positive relationship between CT and motivation. Moreover, the activities of the conventional teaching method were found to be less motivating.…”
Section: Influence Of the Fundamental Concepts Of Ct In Improving Stu...supporting
confidence: 91%
See 1 more Smart Citation
“…The results of this study revealed that the fundamental concepts of CT enhanced students' writing motivation in terms of self-efficacy beliefs, mastery goals, and performance goals more effectively than the conventional teaching method. The results of this study are consistent with those of [4,27], who have reported a significant positive relationship between CT and motivation. Moreover, the activities of the conventional teaching method were found to be less motivating.…”
Section: Influence Of the Fundamental Concepts Of Ct In Improving Stu...supporting
confidence: 91%
“…By contrast, students who are motivated to write may be more likely to take risks and be creative, which can assist them in overcoming their writing anxiety. The authors of [27] stated that motivation could increase students' efforts to improve their writing skills. Therefore, teachers must establish a supportive classroom atmosphere where students do not fear making mistakes and may freely express themselves; such an atmosphere can help to reduce students' writing anxiety and increase their motivation to write.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, writing motivation was positively impacted by treatment, although not statistically significant at the .05 level. Increased motivation may be attributed to strategic and collaborative writing with ongoing feedback (Camacho et al, 2020;Derewianka, 2014;Martín et al, 2020) and having authentic purpose and audience (Magnifico, 2010). However, additional research should be conducted due to the large number of students who had difficulty accessing the language of the survey and were therefore excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Technology-based learning is defined as the use of the internet with a computer or technology-related devices to produce, disseminate, and supply learning materials and regulate course content. Therefore, many schools have implemented technologies to enhance the teaching and learning processes (Ortega, Hameleers, Trujillo-Torres & Moreno-Guerrero, 2020). Teachers can adopt technological strategies to disseminate curricula and guarantee students' access to materials from various disciplines through digital resources.…”
Section: Introductionmentioning
confidence: 99%